Management dialogue - Okoduwa, B. Ebosele (Ikeja, Lagos State, Nigeria : Praskills Nig., 1995)
The purpose of writing this book is to provide practicing managers; intending managers; teachers and students of Management and Business Administration and the general reader a selection of expandable topics to stimulate and challenge discussions.
Includes indexes.
hza 21/09/2018
Loans
Keywords: Management